Physical inactivity and its associated factors among adults in Malaysia : findings from National Health and Morbidity Survey (NHMS) 2019 - Nazirah Alias,; Chan, Ying Ying; Lim, Kuang Kuay; Ahzairin Ahmad,; Halizah Mat Rifin,; Nik Adilah Shahein,; Azli Baharudin, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Physical inactivity has been identified as the fourth leading risk factor for worldwide mortality with major implications towards general health. Monitoring the level of physical inactivity may reduce the burden of non-communicable diseases (NCDs) and their risk factors. This study aims to determine the prevalence of physical inactivity and its associated factors among adults aged 18 years and above in Malaysia. Data was obtained from the National Health and Morbidity Survey (NHMS) 2019. It was a cross-sectional, population-based survey which employed two- stage stratified random sampling design. A total of 10,356 out of 10,472 respondents were interviewed using a short version of International Physical Activity Questionnaire (IPAQ). Overall, the prevalence of physical inactivity among adults aged 18 years and above in Malaysia was 24.6% (95% CI: 23.2, 26.1). Results from multivariable logistic model showed that Chinese ethnicity (aOR 1.32; 95% CI: 1.04, 1.67), urban dwellers (aOR 1.30; 95% CI: 1.07, 1.57), those who were single (including widow, widower and divorcee) (aOR 1.36; 95% CI: 1.14, 1.61), students (aOR 2.10; 95% CI: 1.30, 3.40), higher household income earners (aOR 1.34; 95% CI: 1.07, 1.68) and those with hypercholesterolaemia (aOR 1.25; 95% CI: 1.03, 1.51) were significantly more likely to be physically inactive. Specific and appropriate intervention towards targeted group is in crucial need to increase the level of physical activity and to promote an active living towards an active and healthy Malaysia.